Associations between alliance, physiotherapists' confidence in managing the patient and patient-reported distress in chronic low back pain practice. (4th May 2021) - Brunner, Emanuel; Dankaerts, Wim; O'Sullivan, Kieran; Meichtry, André; Bauer, Christoph; Probst, Michel
Abstract: Purpose: Physiotherapists often feel insecure when managing patients with chronic low back pain associated with psychological factors. This uncertainty could hinder physiotherapists in fostering strong patient-therapist alliances in chronic low back pain practice. The purpose of this study was to explore associations between patient-rated alliance, physiotherapists' self-reported confidence in managing the patient and patient-reported psychological distress. Methods: Patients with chronic low back pain ( N = 21) self-reported their psychological status at baseline. After the intake session, physiotherapists self-reported their confidence (enthusiasm and competence) in managing the patient with chronic low back pain. Patient-rated alliance was measured after the third physiotherapy session. A linear mixed model estimated associations between alliance (dependent variable), physiotherapists' confidence and patient-reported distress. Results: The linear mixed model estimated a positive interaction effect (therapist confidence × patient distress) on patient-rated alliance (estimated effect, β = 0.15; 95% Confidence Interval = 0.03–0.27). Conclusions: Higher self-reported confidence in managing the patient with chronic low back pain by physiotherapists was associated with higher patient-reported alliance after the third physiotherapy sessions. The positive effect between therapist confidence and patient-rated alliance appeared to be dependent on patient-reported psychological distress at baseline.